2021
DOI: 10.3389/fphar.2021.636134
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Endothelium to Achieve Cardioprotection

Abstract: Despite considerable improvements in the treatment of myocardial infarction, it is still a highly prevalent disease worldwide. Novel therapeutic strategies to limit infarct size are required to protect myocardial function and thus, avoid heart failure progression. Cardioprotection is a research topic with significant achievements in the context of basic science. However, translation of the beneficial effects of protective approaches from bench to bedside has proven difficult. Therefore, there is still an unmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 168 publications
(223 reference statements)
0
12
0
2
Order By: Relevance
“…Endothelial cells have been identified as a therapeutic target for treating MI and preventing the progression to heart failure. [55,56] Angiogenesis has been shown to be negatively impacted by MG accumulation, in part through the up-regulation of antiangiogenic factors and dysregulation of VEGF signaling. [57,58] Our in vitro results showed that fisetin-HG can prevent MGinduced defective angiogenesis in cultured endothelial cells, and we observed an increase in arteriole density in the MI mouse model after fisetin-HG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells have been identified as a therapeutic target for treating MI and preventing the progression to heart failure. [55,56] Angiogenesis has been shown to be negatively impacted by MG accumulation, in part through the up-regulation of antiangiogenic factors and dysregulation of VEGF signaling. [57,58] Our in vitro results showed that fisetin-HG can prevent MGinduced defective angiogenesis in cultured endothelial cells, and we observed an increase in arteriole density in the MI mouse model after fisetin-HG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The above evidence, however, suggests that vascular ECs undergo angiogenesis by EVs. Furthermore, endothelialderived EVs could directly contribute to transduce RIC into a proangiogenic output [60]. Early work demonstrated that cultured HUVECs shed EVs, ranging from 300 to 600 nm and containing matrix metalloprotease-2 (MMP-2) and MMP-9, which autocrinally stimulate endothelial migration [61].…”
Section: Endothelium Evs and Angiogenesismentioning
confidence: 99%
“…In addition, increased endothelial permeability and excessive cellular swelling represent critical mechanisms of MIRI. Therefore, endothelial cells are becoming a vital target of multiple therapeutic approaches to MIRI in diabetes [9].…”
Section: Introductionmentioning
confidence: 99%